Rattus rattus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
660. Roof Rat Rattus rattus French: Rat noir / German: Hausratte / Spanish: Rata negra Other common names: Black Rat, Common House Rat, House Rat, Ship Rat Taxonomy. Mus rattus Linnaeus, 1758, “Europe.” Taxonomy of R. rattus and its relatives is currently influx, and the clade might represent 4-6 species in the R. rattus species complex. As currently recognized, six main lineages in the R. rattus clade are recognized as four distinct species: R. rattus (Lineage I, 2n = 38), R. tanezumi (Lineage II, III, and IV, 2n =42 and 2n = 40 in Sri Lankan Lineage IV), R. sakeratensis (Lineage V), and R. tiomanicus (Lineage VI). As currently understood genetically, Lineage I is sister to Lineage II, both of which are sister to Lineage III. The clade containing Lineages I-III aresister to a clade including Lineage IV-VI, Lineage IV and Lineage V being sister to one another with Lineage VI as sister to them both. This phylogeny leaves R. tanezumi paraphyletic. Lineage I and II seem to be the two that spread around the world, with representatives of Lineage I probably originating on the Indian subcontinent and Lineage II probably originating in northern Indochina and Taiwan. Lineage III probably originated from the Himalayan region, and Lineage IV probably originated in the Indomalayan region, both of which are genetically only found in South-east Asia. Karyotype of Lineage III is probably 2n = 42, but specimens from which the karyotype was taken were not included in any genetic study. Lineage IV spread throughout Sundaland (Indomalaysia, Java, and Philippines at least), Sulawesi, and Sri Lanka. This spread was probably proliferated by humans moving through the Australasian region and potentially rafting from Java or another region within the distribution of Lineage IV to Sri Lanka. The Sri Lankan population is rather unique in its karyotype of 2n = 40, which differs from the other populations attributed to Lineage IV, being 2n = 42. Lineage II spread locally through Australasia and then globally. Locally, Lineage II spread ...